(untitled) (Mustansiria Dental Journal, 2018)
This study was designed to assess the microscopical changes of the enamel surface before and following the treatment with different concentration of metal salts, involving zinc, strontium, magnesium, in addition to stannous fluoride and de-ionized water as the control. Microscopic examination was conducted on teeth samples before and following pH-cycling procedure and following the treatment with the selected metal salt under polarized microscope (100X). The best obvious remineralization was found following treatment with stannous fluoride, followed by zinc chloride. Samples treated with strontium chloride showed rather poorly mineralized surfaces. No signs of mineralization were observed for samples treated with magnesium chloride. Although stannous fluoride was the best in the remineralization of initial caries, results for other metals seem to be promising if used for prevention of dental caries